PSIKOEDUKASI PENINGKATAN KETERAMPILAN SOSIAL REMAJA: BAGAIMANA MENJADI ASERTIF? - Auliannisa, Siti Hajar; Ridwan, Rifqah Nur; P, RR Atikah Puspita (LPPM Institut Pendidikan Nusantara Global, 2024)
Social skills, including assertive behavior, are crucial for adolescents to establish healthy and successful social relationships in their surroundings. Psychoeducation is an effective effort in enhancing understanding and application of social skills, including assertive behavior, among adolescents. This study aimed to evaluate the effectiveness of psychoeducation in improving understanding and application of assertive behavior among students of SMA Negeri 18 Makassar. This research method utilized a one group pretest-posttest design with 34 student participants. Data were collected through pretest and posttest using Google Form and analyzed with the Wilcoxon Test. The analysis results indicated a significant improvement (p=0.000 <0.05) in understanding and application of assertive behavior based on the pretest and posttest results. In conclusion, psychoeducation is effective in enhancing understanding and application of assertive behavior among adolescents. Further efforts are needed to strengthen the social skills of adolescents, including assertive behavior, so that they can communicate and interact more effectively with their environment.